Relationships among postpartum maternal body composition, breastfeeding, docosahexaenoic acid (DHA) status, and physical activity - Pendleton, Wesley D., author; Harris, Mary, advisor; Melby, Chris, committee member; Bell, Chris, committee member (Colorado State University. Libraries, 2016)
BACKGROUND: The time periods of pregnancy and lactation are recognized as times of changes in maternal weight and high bone turnover and theoretically can be transitional time periods regarding female body composition. We aim to inquiry associations between postpartum body composition, breastfeeding, maternal docosahexaenoic acid (DHA) status and intake, and physical activity. METHODS: 27 women 37.3 ± 17.3 months postpartum participated. Blood samples were assessed for DHA. DEXA analyses provided body composition data. Pearson’s correlations and linear regression models tested for significance. RESULTS: Total MET hours per week significantly positively correlated with whole body BMD and lumbar BMC. Both physical activity and RBC DHA explained significant amounts of variance within lumbar and pelvic BMC. CONCLUSIONS: Associations between exercise and bone mineralization within the postpartum period were further elucidated, though the role of DHA is still unclear.